A reliable micro-CT-based method reveals dynamic changes to alveolar bone and tooth root following ligature-induced periodontal injury in the mouse - Fu, Yu; Qayyum, Wasif; Shafiei, Parsa; Eaton, Farah; Alexiou, Maria; Graf, Daniel (Bone (New York, N.Y.), 2025)
This study presents a method development and evaluation framework for assessing longitudinally the dynamic alveolar bone changes in a murine periodontal injury model using 3D Slicer software. Accurate and reproducible measurement of bone loss is crucial for periodontal research, yet traditional two-dimensional (2D) histological approaches lack the ability to capture three-dimensional (3D) alterations, while inconsistencies in image alignment, region of interest (ROI) selection, and segmentation have limited the widespread adoption of 3D micro-CT analysis in small animal models. Here, we present a standardized workflow, incorporating defined criteria for ROI selection, scan alignment, and segmentation suitable for live micro-CT scanning. We validated this method using the ligature-induced periodontal injury model in mice. Multiple micro-CT scans were performed over 35 days to evaluate changes to alveolar bone and tooth roots. Quantitative analysis highlighted significant bone loss and early-stage remodeling within the first two weeks. Following ligature removal at 3 weeks, bone loss largely resolved by the end of week 5. However, we find that although the total bone volume mostly recovers, permanent changes at the alveolar crest persist, and additional cementum was formed at the apical tooth root. By enhancing methodological consistency, this standardized protocol improves the accuracy and comparability of longitudinal studies and minimizes variability in small animal studies, providing a reliable framework for functional investigations. Through its application, we show for the first time that, beyond alveolar bone regeneration, cementum apposition at the root apex is also observed. This opens up studies investigating how root loss at the apex could be restored. •Developed reproducible method for alveolar bone assessment from micro-CT scans•Landmarks and ROI selection ensure high reproducibility, suitable for longitudinal studies.•Application to the ligature model of periodontal injury identifies waves of bone regeneration.•Regenerated bone does not fully match height and shape of bone prior to injury.